Analysis of the Effect of Service Quality on Student Satisfaction - Makmun - Riyanto; Putut - Haribowo; Sri - Wahyuni; Taviyastuti - Taviyastuti; Rustono - Rustono (Admisi dan Bisnis, 2022)
This is important to know as an evaluation and improvement effort if there is something that needs to be improved and student satisfaction will create a good image for the institution, and a good image will create loyalty and pride of students in the Polines as an alma mater. This study is intended to find out how the level of student satisfaction over the service facilities of the Polytechnic Language Unit, as well as what factors influence student satisfaction with the service of the UPT  Bahasa Polines. The results of this study are expected to provide useful input for managers of health clinics in particular and Polines to be able to provide satisfactory services to students as their main consumers.Based on descriptive analysis using index analysis techniques (index value) and using the three-box criteria (three box method) it is known that all service quality variables (Tangible, reliability, responsiveness, assurance, empathy) are perceived high (good) by the respondents. The results of the quantitative analysis of the study also showed that the service quality of the UPT Bahasa Semarang State Polytechnic  consisting of Tangible (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), Empathy (X5) had a positive effect on student satisfaction(Y), but the only significant effect is the Assurance variable (X4), and Empathy variable (X5).To increase student satisfaction, it is recommended to the manager of theUPT Bahasa Polines by increasing the elements as in the indicators of the two variables, namely Empathy variable (X5): Attention and sincerity of officers / lecturers in the UPT Bahasa Polines  in accepting and serving visitors. good, convincing and polite by not discriminating, notifying the results of learning development / test results and providing suggestions for successful learning,Whereas for the Assurance variable (X4) : Competency, education and appropriate and adequate experience of officers and instructors of UPT Bahasa Polines, Hospitality in welcoming and serving thus giving rise to feelings / beliefs as the right place of service, Completeness of learning support facilities such as projectors, books,  audio video, language equipment / laboratory so that it can guarantee the success of learning.